LINGUISTIC AND PRAGMATIC ANALYSIS OF SPEECH ETIQUETTE IN GERMAN AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2025)
This article presents a linguo-pragmatic analysis of speech etiquette in German and Uzbek cultures. The study examines the cultural, social, and historical foundations of speech etiquette and its role in intercultural communication. Precision and formality dominate German culture, whereas sincerity and hospitality are key principles of Uzbek culture. The results of the comparative analysis offer scientific recommendations for strengthening intercultural connections and enhancing effective communication. The research aims to deepen the understanding of the importance of speech etiquette in the context of globalization.